A selective serotonin receptor agonist for weight loss and management of menopausal vasomotor symptoms in overweight midlife women: a pilot study. Issue 11 (November 2020) - Kapoor, Ekta; Faubion, Stephanie; Hurt, Ryan T.; Fischer, Karen; Schroeder, Darrell; Fokken, Shawn; Croghan, Ivana T.
Abstract: Objective: Weight gain and vasomotor symptoms (VMS) are common complaints in midlife women going through the menopause transition. A selective serotonin 2C (5-HT2C) receptor agonist, lorcaserin, which was previously approved by the Food and Drug Administration for weight loss, has unreported observational evidence suggesting improvement in VMS with its use. The goal of this pilot study was to evaluate the efficacy of lorcaserin for weight loss and management of VMS in overweight midlife women. Methods: This was a 24-week open label pilot study of 20 overweight midlife women, aged 45-60 years, who were experiencing severe VMS. Participants received lorcaserin at the standard dose of 10 mg twice daily for 12 weeks, followed by 12 weeks of observation off the drug. The primary outcomes were changes in weight and subjectively reported VMS. Results: At the end of 12 weeks, mean change in weight was −2.4 kg (90% CI, −3.2 to −1.7, P < 0.001). However, the participants returned to the baseline weight at 24 weeks. Participants also reported significant subjective improvement in VMS, with a mean ± SD change in self-reported hot flash frequency from baseline to week 12 of −5.4 ± 3.9 (decrease of 1.4 standard deviations). There was a rapid increase in the frequency of VMS within 2 weeks of discontinuation of lorcaserin with a tendency to approach the baseline frequency of VMS. Conclusions: In addition to its weight loss-inducing effect, 5-HT2C receptor modulation may have an additional beneficial effect on VMS in midlife women. A treatment option that targets both weight and VMS in midlife women is attractive. N/A: Video Summary: http://links.lww.com/MENO/A622 . Abstract : Supplemental Digital Content is available in the text